Cellular effects of heavy metals - Banfalvi, Gaspar; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
The term 'heavy metals' is used as a group name of toxic metals and metalloids (semimetals) causing contaminations and ecotoxicity. In strict chemical sense the density of heavy metals is higher than 5 g/cm3. From biological point of view as microelements they can be divided into two major groups. a. For their physiological function organisms and cells require essential microelements such as iron, chromium (III), cobalt, copper, manganese, molidenium, zinc. b. The other group of heavy metals is toxic to the health or environment. Of highest concern are the emissions of As, Cd, Co, Cu, Hg, Mn, Ni, Pb, Sn, Tl. The toxicity of heavy metals is well known at organismal level, while less attention has been paid to their cellular effects. This book describes the toxicity of heavy metals on microorganisms, yeast, plant and animal cells. Other chapters of the book deal with their genotoxic, mutagenic and carcinogenic effects. The toxicity of several metals touch upon the aspects of environmental hazard, ecosystems and human health. Among the cellular responses of heavy metals irregularities in cellular mecha nisms such as gene expression, protein folding, stress signalling pathways are among the most important ones. The final chapters deal with biosensors and removal of heavy metals. As everybody is eating, drinking and exposed to heavy metals on a daily basis, the spirit of the book will attract a wide audience.
Heavy metals, trace elements and their cellular effects / Gâaspâar Bâanfalvi -- Toxic metal/metalloid tolerance in fungi : a biotechnology-oriented approach / Istvâan Pâocsi -- Interference of chromium with cellular functions / Borut Poljsak, Istvâan Pâocsi and Miklâos Pesti -- Saccharomyces cerevisiae as a model organism for elucidating arsenic tolerance ́́mechanisms / Robert Wysocki and Markus J. Tamâas -- Heavy metal toxicity in an insect cell line (methyl-HgCl, HgCl₂, CdCl₂, and CuSO₄) / Bart P. Braeckman -- Cellular changes in mammalian cells induced by cadmium / Gâaspâar Bâanfalvi -- Chromatin toxicity of Ni(II) ions in K562 erythroleukemia cells / Gâabor Nagy ... [et al.] -- Genotoxic chromatin changes in schizosaccharomyces pombe induced by hexavalent chromium (CrVI) ions / Gâabor Papp ... [et al.] -- Chromatin changes upon silver nitrate treatment in human keratinocyte HaCaT and K562 erythroleukemia cells / Gâabor Nagy ... [et al.] -- Heavy metal-induced carcinogenicity : depleted uranium and heavy-metal tungsten alloy / John F. Kalinich -- Role of oxidative damage in metal-induced carcinogenesis / Kazimierz S. Kasprzak -- Non-native proteins as newly-identified targets of heavy metals and metalloids / Sandeep K. Sharma, Pierre Goloubinoff and Philipp Christen -- Cellular mechanisms to respond to cadmium exposure : ubiquitin ligases / Karin Flick and Peter Kaiser -- Metals induced disruption of ubiquitin proteasome system, activation of stress signaling and apoptosis / Xiaozhong Yu, Rafael A. Ponce and Elaine M. Faustman -- Blood lead level (BLL, B-Pb) in human and animal populations : B-Pb as a biological marker to environmental lead exposure / Nelly Maänay, Adriana Cousillas and Teresa Heller -- Removal of heavy metal sulfides and toxic contaminants from water / Gâabor Szalâoki ... [et al.].
Electronic reproduction.
Keywords: Heavy metals -- Physiological effect; Heavy metals -- Toxicology; Electronic books